LINE1 contributes to autoimmunity through both RIG-I- and MDA5-mediated RNA sensing pathways. (June 2018) - Zhao, Ke; Du, Juan; Peng, Yanfeng; Li, Peng; Wang, Shaohua; Wang, Yu; Hou, Jingwei; Kang, Jian; Zheng, Wenwen; Hua, Shucheng; Yu, Xiao-Fang
Abstract: Improper host immune activation leads to the development of the autoimmune disease Aicardi-Goutières syndrome (AGS), which is attributed to defined genetic mutations in such proteins as TREX1 and ADAR1. The mechanism of immune activation in AGS patients has not been thoroughly elucidated to date. In this study, we report that endogenous LINE1 components trigger IFNβ production in multiple human cell types, including those defective for cGAS/STING-mediated DNA sensing. In these cells, LINE1 DNA synthesis and retrotransposition were not required for LINE1-triggered immune activation, but RNA sensing pathways were essential. LINE1-triggered immune activation could be suppressed by diverse LINE1 inhibitors, including AGS-associated proteins targeting LINE1 RNA or proteins. However, AGS-associated ADAR1 or TREX1 mutants were defective in suppressing LINE1 retrotransposition or LINE1-triggered immune activation. Therefore, we have revealed a new function for LINE1 as an endogenous trigger of innate immune activation, which is important for understanding the molecular basis of IFN-based autoimmune diseases and may offer new intervention strategies. Highlights: Manipulating endogenous LINE1 alters IFNβ production in multiple human cell lines. LINE1 components activate both RIG-I- and MAD5-mediated RNA sensing pathways. LINE1-induced IFNβ production is reduced by proteins linked to autoimmune diseases. LINE1-triggered innate immune activation contributes to autoimmunity development. Suppressors targeting LINE1 RNA/proteins function as innate immune regulators.